Scalp Reconstruction among Neurotrauma Patients: Presentation, Management and Outcome- Single Center Study - Thapa, Dinesh Kumar (Eastern Green Neurosurgery, 2020)
Background: Scalp laceration is common findings among patients with head injury. It may present with simple laceration, laceration with loss of tissue or degloving type of injury. This study was conducted to observe the different techniques or wound management and fate of thus reconstructed scalp lacerations. Methods and materials: This is a cross-sectional analytical study which was conducted in B&C Medical College Teaching Hospital, Jhapa, Nepal. Patients presented with major scalp lacerations needing repair in Operation Theatre between June 2017 to May 2019 were included. Age, gender, mode of injuries, severity of the injury, various types of management and complicationswere studied and thus collected data were analyzedin IBM SPSS version 23. Results: There were 53 cases of scalp injuries with male(75%) predominance and mean age of 31.51 (SD 15.218) yearsin this study. Road traffic accident was the major cause of injury 28(53%), followed by physical assault 16(30%), fall injury 7(13.2%) and burn injury 2(3.7%).Primary closure was possible in 29(54.7%), advancement flap in15(28.3%), flap rotation in 7(13.2%) and split thickness skin graft was in 2(3.8%) patients. Wound infection was seen among 6(11.3%) patients, wound break down in 2(3.7%) and flap failure with dehiscence was observed in 1(1.9%) patient needing secondary healing and closure. Conclusion: Scalp laceration is commonly seen in neurotrauma patients with or with-out intracranial injury. Road traffic accidents top the chart in our part of world.All kinds of scalp laceration can be managed well with different types of surgical techniques.